Soil bacterial community is more sensitive than fungal community to canopy nitrogen deposition and understory removal in a Chinese fir plantation - Xi, Dan; Jin, Shaofei; Wu, Jianping (Frontiers in Microbiology, 2022)
Soil microorganisms are key regulators for plant growth and ecosystem health of forest ecosystem. Although previous research has demonstrated that soil microorganisms are greatly affected by understory nitrogen (N) addition, little is known about the effects of canopy N addition and understory management on soil microorganisms in forests. In this study, we conducted a full designed field experiment with four treatments: canopy N addition (CNA, 25 kg N ha-1yr-1), understory removal (UR), canopy N addition, and understory removal (CNAUR, 25 kg N ha-1yr-1), and control in a Chinese fir plantation. High-throughput sequencing and qPCR techniques were used to determine the abundance, diversity, and composition of bacterial and fungal communities in three soil layers. Our results showed that CNA increased bacterial diversity in the 10-20 cm soil layer but decreased bacterial abundance in the 20-40 cm soil layer and fungal diversity in the 0-10 cm soil layer. UR increased bacterial abundance only in the 20-40 cm soil layer. CNA, not UR significantly altered the compositions of soil bacterial and fungal community compositions, especially in the 0-20 cm soil layer. CNA sharply reduced the relative abundance of copiotrophic taxa (i.e., taxa in the bacterial phylum Proteobacteria and the orders Eurotiales and Helotiales in the fungal phylum Ascomycota) but increased the relative abundance of oligotrophic taxa (i.e., in the bacterial phylum Verrucomicrobia). RDA analysis revealed that soil pH, DON, and DOC were the main factors associated with the variation in bacterial and fungal communities. Our findings suggest that short-term CNA changes both soil bacterial and fungal communities, with stronger responses in the surface and middle soil than in the deep soil layer, and that UR may enhance this effect on the soil bacterial abundance. This study improves our understanding of soil microorganisms in plantations managed with understory removal and that experience increases in N deposition.